DSTATCOM-BASED 15 LEVEL ASYMMETRICAL MULTILEVEL INVERTER FOR IMPROVING POWER QUALITY - Sundaramoorthi, Panneerselvam; Venkatesh, Govindasamy Saravana (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2024)
This study suggests an asymmetric multilevel inverter based on DSTATCOM that employs SVPWM techniques to produce higher output levels. There are two steps in the suggested inverter. One full bridge and two half bridges make up the inverter's main stage. A full bridge converter had four switches and a single DC source, while half bridges have separate DC sources with a voltage ratio of 1:3:3. Every cell has a fixed neutral point and is connected in a cascaded fashion. The inverter's performance is not improved by setting the DC source values equally. A folded cascaded H-bridge circuit running at a line frequency makes up the second circuit. Control plan PWM's space vector modulation was used to verify the suggested topology. Each control scheme's specific methodology as well as switching pulses are covered in great detail. In MATLAB/Simulink, the suggested system has been simulated with an output voltage of 350 V and an output current of roughly 3.5 A.